2014
DOI: 10.1002/art.38771
|View full text |Cite
|
Sign up to set email alerts
|

Altered White Matter Integrity in the Corpus Callosum in Fibromyalgia Patients Identified by Tract‐Based Spatial Statistical Analysis

Abstract: Objective. Although recent imaging studies of fibromyalgia (FM) have converged on a dysfunction of central pain processing as the primary pathophysiologic cause of the disorder, microstructural changes of the white matter (WM) suggestive of abnormalities in the anatomic connectivity of the brain have not been extensively examined. The aim of this study was to investigate WM integrity and its possible relationship to pain symptoms in women with FM.Methods. Nineteen FM patients and 21 age-, sex-, and education-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 52 publications
0
33
1
Order By: Relevance
“…Reduced FA in the thalamus was also reported in a third study (n=19) that correlated with pain reporting [70]. Recently, contrarian findings of reduced FA that correlated with increases in pain reporting were found in 19 patients in the portion of the corpus callosum that connects to S1 [71]. Age also appears to be an important factor in anisotropy in FM.…”
Section: White Matter Alterations In Fibromyalgiamentioning
confidence: 65%
“…Reduced FA in the thalamus was also reported in a third study (n=19) that correlated with pain reporting [70]. Recently, contrarian findings of reduced FA that correlated with increases in pain reporting were found in 19 patients in the portion of the corpus callosum that connects to S1 [71]. Age also appears to be an important factor in anisotropy in FM.…”
Section: White Matter Alterations In Fibromyalgiamentioning
confidence: 65%
“…The main interhemisphere commissure is required for many aspects of neural function, encompassing inhibition of cortical functions, integration of sensory information, regulation of cognition, processing of emotion, and interhemispheric exchange of information. 52,53 Multiple studies reported CC dysfunction in patients with chronic pain, such as fibromyalgia, 54 migraine, 55 and temporomandibular disorder, 56 supporting the indicative role of the CC in pain perception and pain control. 57 Therefore, we reasoned that aberrations in the WM integrity in the CC may cause the reduction of obstruction to water diffusion and reduced anisotropy, which can be responsible for the perceptional intensity of abdominal discomfort and pain in FC and IBS-C patients.…”
Section: Discussionmentioning
confidence: 90%
“…Association fibers, namely (6) the cingulum cingulate gyrus (i.e., subgenual and retrosplenial part of the cingulum) and (7) the cingulum hippocampus (i.e., parahippocampal part of the cingulum) (Lieberman et al, ; Mori et al, ) and (8) fornix and stria terminalis (Borsook et al, ; Chen et al, ; Upadhyay et al, ). Finally, commissural fibers, that is (9) the tapetum of the corpus callosum (Kim et al, ; McAllister, ) and (10) the splenium of the corpus callosum (Lieberman et al, ). Acceleration–deceleration of the brain is believed to affect the superior cerebellar peduncles, and periventricular WM (McAllister, ), for example, tapetum of the corpus callosum (Kim et al, ; Sarikcioglu et al, ; Todd & Lempert, ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, commissural fibers, that is (9) the tapetum of the corpus callosum (Kim et al, ; McAllister, ) and (10) the splenium of the corpus callosum (Lieberman et al, ). Acceleration–deceleration of the brain is believed to affect the superior cerebellar peduncles, and periventricular WM (McAllister, ), for example, tapetum of the corpus callosum (Kim et al, ; Sarikcioglu et al, ; Todd & Lempert, ). For visualization purposes, masks of these ROIs are displayed on MD maps of the WM Mori atlas (Mori et al, ) in Figure .…”
Section: Methodsmentioning
confidence: 99%